ASOSIASI KONINKLIJKE JAVA MOTOR CLUB TAHUN 1908-1941 - Elita, Karina Sandra (History Department, Faculty of Humanities, University of Jember, 2024)
This research discusses the association of Koninklijke Java Motor Club from 1908 to 1941. The basis of the theory used is organizational theory. The issue studied is (1) How the development of membership and the composition of membership of the Koninklijke Java Motor Club association in the Dutch East Indies, (2) What activities the Koninklijke Java Motor Club association conducted in the Dutch East Indies in 1908 to 1942, (3) How the Koninklijke Java Motor Club association cooperated with other associations both in the Dutch East Indies and outside the Dutch East Indies. The results showed that the Koninklijke Java Motor Club is a society of people who own motor vehicles (either cars or motorcycles) in the Dutch East Indies, this association belongs to the Kingdom of the Netherlands.The development of the number of members of the Koninklijke Java Motor Club from 1908 to 1941 showed fluctuating, this was due to the malaise crisis in 1930. Initially, Koninklijke Java Motor Club activities only in Java Island then developed in Sumatra, Bali, and Sulawesi.With the widespread activities of Koninklijke Java Motor Club outside Java Island decided to change the name of the association to Koninklijke Nederlandsch Indie Motor Club in December 1932. It can be concluded that Koninklijke Nederlandsch Indie Motor Club is an association oriented towards the hobbies and tourism activities of the Dutch East Indies. Keywords: Koninklijke Java Motor Club; Dutch East Indies; Association; Koninklijke Nederlandsch Indie Motor-Club